ANALISIS PERAN FILSAFAT IDEALISME SERTA IMPLEMENTASINYA PADA PENDIDIKAN - Puspitasari, Leni; Idawati, Idawati; Patta, Nur Fitrah Julianti; Indana, Nabila (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Idealism asserts that the mind, soul, or spirit is superior to material objects. In education, idealism plays a key role in shaping standards that develop students' intellectual, moral, and spiritual aspects. This philosophy forms the foundation for character development and knowledge acquisition based on essential values. This study analyzes the role of idealist philosophy in education and its implementation in learning systems. Using a library research method, relevant sources such as books, journals, and online materials were examined. The collected data was classified and analyzed descriptively to understand how idealism contributes to education. Findings indicate that idealist philosophy enhances education by emphasizing character formation, understanding universal concepts, and achieving absolute truth through reflection. It promotes not only cognitive growth but also moral and spiritual development. In practice, idealism is reflected in dialogical learning, ethical reinforcement, and deeper philosophical integration. It significantly impacts education by building a system that values intellect and morality. Applying idealist principles fosters a more holistic and meaningful learning experience. This study affirms that idealism-based education remains relevant in addressing modern educational challenges, shaping individuals with broad perspectives rooted in truth and virtue.